Traditional Māori leadership and its relevance for 2020 vision : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Advanced Leadership Practice at Massey University, Albany, New Zealand - Taylor, Gavin Geoffrey (Massey University, 2020)
This research examines the relevance of traditional Māori leadership concepts and practices through investigating the commonalities and differences that exist with contemporary Māori leadership. Currently, there is some debate regarding the value of traditional Māori leadership principles during contemporary times, and this study contributes to those discussions. In this study, I look at traditional Māori leadership through the eyes of one of the most prominent Māori leaders from a past era—Te Rauparaha as a case study, and I use semi-structured in-depth interviews with four contemporary Māori leaders to garner leadership traits. Taking an inductive approach that utilises interpretivist and kaupapa Māori methodology paradigms, I investigate the tensions that Māori leadership faces entering a new decade, 180 years on from the signing of the Treaty of Waitangi. My research shows that the core principles of Māori leadership remain entirely relevant in a contemporary context. The findings highlight the vital role a leader has within Māori society, whether it is with family, extended family or within the broader kindred community at a tribal level, as well as in non-Māori contexts. Māori leaders past and present, view people as their highest priority. They are not a commodity or currency but those for whom a leader must provide, protect, and care for through their leadership skills and abilities. There is a range of issues facing Māori leadership today, which makes traditional Māori values appear less prevalent; however, beliefs such as unity, hospitality, reciprocity, legacy and gender roles still have relevance and hold meaning for Māori. The signing of the Treaty of Waitangi has not future-proofed Māori from leadership uncertainty, nor non-Māori hegemonic control, but it is evident that when Māori remain steadfast to their ethnicity and te ao Māori (the Māori world), they can ensure that Māori leadership for their people and people in general, has a place in the future.
Keywords: 350707 Leadership; 450707 Te ahurea Māori (Māori culture)